(untitled) (Sociologisk Forskning, 2008)
In the home of others: exploring new sites and methods when investigating the doings of gender, class and ethnicity What role does the experience of being in and observing other people’s home play informing one’s gender and class identities and family aspirations? And how can it be explored? Through the traditions of socialization theory the everyday/-night experiences of family life are objectified into an institution (the family) with abstracted relations (mother-father-child) and functions (”primary socialization”). This is a view directly related to ruling relations through which the family is institutionalized, by rules and regulations, and made accountable as such. Hereby the question of experiences of other sites (and localities!) and other relations when forming one’s gender and family aspirations are not raised. In this article it is argued that when using an alternative approach (the method of inquiry proposed by Dorothy E. Smith) and alternative methods (memory work) the door to other homes is opened. Using experience stories a picture is drawn where new sites and relations are made visible as crucial contexts where gender and family life is explored and learned. By illuminating the ”work knowledge” of family life another way of mapping is presented, a way that extends and transforms the traditions within family research.